TINJAUAN KAPASITAS ABUTMEN JEMBATAN SENGKALING MALANG DENGAN BEBAN GEMPA - Nindi Rizki Apriliani; Pujo Priyono; Arief Alihudien (HEXAGON, 2020)
lower. This obstacle is usually another way such as roads water or ordinary traffic. On planning and bridge work Planning the Structure of the Bottom can not be ignored.Part of the bridge structure is located at the bottom of very decisive for the strength and security of the building thereon.And for a direct link between the structure of the bridge structure under the bridge is the “Abutment” which is included on the structure under the bridge.Abutments of a building that serves to continue the load.Loading code that is used to plan bridge this refers to Indonesian National Standard SNI 1725:2016.The intensity of the earthquake is greatly increased, cause a change in the planning of bridges, the changes contained in the regulation SNI 2833:2016 about planning for earthquake resistance of the bridge. Bridge Sengkaling is a bridge alternative to ease the traffic toward Sengkaling Recreational Park located in Malang, East Java. With a length of28m and a width of 10m this is behind the University of Muhammadiyah Malang.